COMPARISON OF PUBLIC POLICY DEFENSES IMPLEMENTATION IN INDONESIA WITH USA AND UK - Ewangga, Sandy Octavian (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2022)
This article tried to compare the implementation of public policy defenses in the United Kingdom (“UK”) and the United States of America (“USA”). Indonesia has been alleged of being unfriendly to foreign arbitral awards, one of the reason is the implementation of public policy defenses that is interpreted broadly and not restrictively. Even though Indonesia has ratified the New York Convention that supports pro-enforcement bias with Presidential Decree No. 34 of 1981, Indonesia is still far away to be considered a pro-enforcement state compared to the UK and the USA. This article discusses how Indonesia interprets the public policy doctrine from the cases that are provided in this article. The method used in this article was a comparative study, describing the implementation of public policy in the UK and USA. This article concluded that the implementation of public policy in Indonesia is too broad and uncertain, the court can refuse the enforcement of the arbitral awards by only relying on violation of Indonesian laws. Different from the implementation in the UK and USA that established the mere violation of state’s law cannot be considered necessarily as the violation of public policy doctrine. This article is also commenting on how Indonesia modified the implementation of public policy by using the main ground reasons why the arbitral awards were refused by the court.